"Freedom to go where I want": improving access to sexual and reproductive health for women with disabilities in the Philippines. Issue 50 (12th June 2017) - Devine, Alexandra; Ignacio, Raquel; Prenter, Krystle; Temminghoff, Lauren; Gill-Atkinson, Liz; Zayas, Jerome; Marco, Ma Jesusa; Vaughan, Cathy
Abstract: Women with disabilities experience a range of violations of their sexual and reproductive rights. The Philippines ratified the United Nations Convention on the Rights of Persons with Disabilities and have laws in place to promote the rights to sexual and reproductive health and protection from violence. However, limited resourcing, and opposition to such laws undermine access to these rights for all women. Inadequate disability inclusion within policy and programming, and limited disability awareness of services, further impedes women with disabilities from attaining these rights. The W-DARE project (Women with Disability taking Action on REproductive and sexual health) was a three-year participatory action research program designed to (1) understand the sexual and reproductive health experiences and needs of women with disabilities; and (2) improve access to quality sexual and reproductive health, including violence response services, for women with disabilities in the Philippines. In response to the highlighted need for more information about sexual and reproductive health and greater access to services, the W-DARE team developed and implemented a pilot intervention focused on peer-facilitated Participatory Action Groups (PAGs) for women with disabilities. This paper focuses on the qualitative findings from the evaluation of this PAG intervention.